ANALISIS PERUBAHAN GARIS PANTAI PADA BAGIAN HILIR DAS BATANG ANAI - Vir Diannisa Zahra; Widya Prarikeslan (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to analyze the relationship of land cover change to sedimentation rates and their effect on the coastline in the Batang Anai watershed in 1988, 2003 and 2018. The method used is descriptive quantitative, namely determining land cover and coastline by means of digital interpretation of the image on screen. , to analyze the value and area of ​​sediment distribution using the Total Suspended Solid method (Jaelani, 2016), and to get the change value, the overlay method is used and then calculated through calculate geometry. The results showed that the effect of land cover changes on the level of shoreline change in the Batang Anai watershed was <50% and the remaining percentage was influenced by other variables. And it is also proven that the presence of sedimentation strengthens the influence of changes in land cover area on changes in coastline area. Keywords: Change, Land Cover, Sedimentation, Coastlin.